The opportunities and challenges of Industry 4.0 for industrial development: A case study of Morocco's automotive and garment sectors - Georgeta Vidican Auktor (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
The development and application of advanced manufacturing technologies (known as Industry 4.0) have been enabled by the fast-paced process of digital transformation. These transformations are expected to have major implications on the reorganisation of global value chains as well as on labour markets. For late-industrialising countries, Industry 4.0 brings both opportunities and challenges. On the one hand, it opens opportunities in terms of improving competitiveness, learning and export markets. On the other hand, however, it may devalue the traditional competitive advantage based on low labour costs, creating difficult-to-tackle challenges on labour markets related to unemployment and new demands for reskilling and upskilling. This paper explores these aspects through the lens of one country, Morocco, and two very different sectors: automotive and apparel. Morocco is a lower-middle-income country that has capitalised on its proximity to Europe and succeeded in developing a dynamic export-oriented automotive industry. The garment sector, which is critical for employment, has been generally neglected by the industrial development strategies. However, Industry 4.0 and its implications on global value chains are likely to affect both sectors, although in different ways. Our analysis clearly shows that interventions must be tailored to the different degrees of technological readiness. The automotive sector is driven more by the needs of major original equipment manufacturers. Therefore, industrial policy should focus on setting the framework conditions, enabling upgrading by investing in research and development, and shifting incentives towards facilitating local suppliers to better integrate with higher-tier suppliers. In the garment sector, policy interventions need to be more comprehensive, from developing a long-term vision to building awareness on technological upgrading and new business models enabled by digitalisation and automation. Moreover, there is extensive scope for industrial policy to contribute to building basic technological and knowledge capabilities all along the garment supply chain and to attracting investment.
Keywords: 330; industry 4.0; Morocco; automotive; garment